Amelia Bedelia road trip! - Parish, Herman; Avril, Lynne, 1951- (New York, NY : Greenwillow Books, 2013)
Fun and fiascoes ensue when young Amelia Bedelia and her parents take a road trip through their state.
3.1
K-3
640L
Keywords: Automobile travel -- Fiction; Vacations -- Fiction; Family life -- Fiction; Humorous stories; Automobile travel -- Fiction; Vacations -- Fiction; Family life -- Fiction; Humorous fiction; Humorous fiction